Application of problem-based learning combined with a virtual simulation training platform in clinical biochemistry teaching during the COVID-19 pandemic - Xie, Hongxiang; Wang, Li; Pang, Zhenzhen; Chen, Sufeng; Xu, Guoying; Wang, Sumei (Frontiers in Medicine, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic has had a great impact on the traditional teaching mode (Lecture-based Learning, LBL) and laboratory teaching. To address this challenge, the researchers conducted online Problem-based learning (PBL) teaching and virtual simulation laboratory teaching through DingTalk, and evaluated the effectiveness of this method in teaching clinical biochemistry. Methods With the method of cluster sampling, the researchers randomly selected 60 students from two classes of the Class 2019 as the experimental group for this prospective experimental study. The theory class was taught online PBL through DingTalk, and experimental lectures were given by virtual simulation. After the experimental teaching, students were assessed for theory and operation. Self-administered questionnaires were administered through DingTalk. 65 students from our 2018 medical laboratory class were randomly selected as the control group, and offline LBL and traditional experimental teaching methods were used. Examination results were obtained through teaching portfolios. Results The experimental group had significantly better examination scores in theoretical knowledge and experimental operational skills than the control group (87.45 ± 5.91 vs. 83.52 ± 9.94, P = 0.0095; 87.08 ± 12.42 vs. 80.18 ± 14.04, P = 0.0044). The results of the questionnaire survey revealed that the experimental group was more receptive to the DingTalk-PBL teaching method and virtual simulation laboratory teaching. Moreover, this hybrid teaching method was more effective in promoting basic knowledge understanding (95.0%, 57/60), facilitating the mastery of operational skills (93.3, 56/60), cultivating interest in learning (96.7%, 58/60), training clinical thinking (95.0%, 57/60), improving communication skills (95.0%, 57/60), and enhancing self-learning ability (91.7%, 55/60) and was more satisfying than traditional teaching method (all P < 0.05). Conclusion The DingTalk-based PBL method combined with virtual simulation experiments was an effective and acceptable teaching strategy during the pandemic compared with the traditional teaching method.